Student dropout and persistence in universities in Latin America and the Caribbean: a mixed systematic review - Chiarino, Nicolás (2024)
Higher education is a key human right to individuals' and societies' development. Latin America and the Caribbean have higher dropout rates than other regions. This article presents an exhaustive review of the evidence on student dropout and permanence in Latin American and Caribbean universities between 1992-2022. A mixed systematic review was carried out following the guidelines of the PRISMA protocol. 217 studies were identified that met the defined criteria. In consideration of the complex nature of the phenomenon, an ecological approach was adopted by grouping the evidence into 67 variables and four levels: subject, institution, educational system and macrosocial context. Most studies focus on the subject level, followed by the institutional level. Research linked to abandonment predominates (76%) compared to those focused on permanence (24%). Studies with quantitative methodology (76%) prevailed over qualitative (10%) and mixed (14%). 25% of the works had an explanatory scope, where descriptive and correlational studies predominate. Which shows the need to increase the complexity of methodological designs. The findings provided an updated evidence map on dropout and permanence in Latin American and Caribbean higher education. Contributions also promote the development of future research, meaningful guidelines for the construction of early warning systems aimed at the prevention of dropout, and keys for the design of institutions that favor student permanence at the university level.